Power of Knowledge and Community Social Class above Covid-19 Pandemic Information on Social Media - Tri Sulistyaningtyas; Jejen Jaelani; Yani Suryani (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2020)
Information about the spread of the coronavirus is circulated through various information channels in the society, both mainstream media, alternative media, social media, and daily conversation. One of the information channels that is widely used and referenced by the public is social media. Dissemination of information about the expanse of the coronavirus on social media is arranged by various individuals. This study will explain the disemination of information relating to covid-19 in terms of the social class of the reader. In this study, we use critical discourse analysis as a method for analyzing data. This study finding is that the information circulation about coronavirus in social media is class bias. General information is conducted through formal language by middle-class groups. On the other hand, many people present alternative information in the form of memes, jokes, and funny content that contains information about spreading the coronavirus. This phenomenon can be categorized as a lower social class attempt to understanding and spreading information about the coronavirus (Cinelli, et al., 2020)outbreak. The media used to disseminate this information contains text, images/photos, or videos that contain memes, organizes, and funny content. This phenomenon can be seen as a lower-class struggle to educate its class in situations and conditions caused by the coronavirus.